Endothelial function measured using flow‐mediated dilation in polycystic ovary syndrome: a meta‐analysis of the observational studies. (25th January 2013) - Sprung, Victoria S.; Atkinson, Greg; Cuthbertson, Daniel J.; Pugh, Christopher J. A.; Aziz, Nabil; Green, Daniel J.; Cable, N. Timothy; Jones, Helen
Abstract Objective Women with polycystic ovary syndrome (PCOS) demonstrate an increased prevalence of cardiovascular disease (CVD) risk factors. Previous researchers have compared flow‐mediated dilation (FMD), an early marker of CVD, in women with and without PCOS. Evidence for a PCOS‐mediated reduction in FMD remains equivocal, potentially because of study differences in cohort‐matching and measurement approaches. The aims of this systematic review and meta‐analysis were to examine to what extent FMD is impaired in PCOS and to explore the influence of potential moderators of FMD reduction, such as age and BMI. Design A systematic review and meta‐analysis of published observational studies comparing FMD in PCOS with control women. Patients Twenty‐one published studies were included (PCOS, n = 908; controls, n = 566). A subanalysis, using tighter inclusion criteria, involved seven studies (PCOS, n = 402; control, n = 251). Measurements Mean differences in FMD between PCOS and controls were synthesized. The subanalysis was delimited to the inclusion of age and BMI‐matched controls. These factors were then explored as moderators using meta‐regression. Results The pooled mean FMD was 3·4% (95% CI=1·9, 4·9) lower in PCOS compared with control women, with substantial heterogeneity between studies. In the subanalysis, the PCOS‐mediated reduction in FMD was 4·1% (95% CI=2·7, 5·5). Heterogeneity remained substantial (I2=81%). Subsequent meta‐regression indicated that the magnitude of FMD difference was not influenced by BMI (P = 0·17) nor age (P = 0·38). Conclusions This systematic research synthesis indicates that endothelial function is compromised in PCOS women, even if they are young and nonobese.